EFFECTS OF GARLIC (ALLIUM SATIVUM L.) SUPPLEMENTATION ON THE BLOOD PROFILE OF JERSEY CROSSBRED CALVES - N. Balamurugan; S. Meenakshi Sundaram; T. Sivakumar; J.S.I. Rajkumar (Indian Journal of Veterinary and Animal Sciences Research, 2024)
A trial was conducted to assess the influence of different methods of garlic supplementation on the blood profile of crossbred calves. For studying the blood profile, 18 Jersey crossbred calves of both sexes in the age group of 2-3 months were randomly allotted into three treatment groups of 6 calves in each group. Calves in the first group (T1) were supplemented with garlic powder at the dose rate of 250 mg/Kg BW for a period of 150 days in water whereas calves in the second group (T2) were supplemented with 250mg/Kg BW in concentrate feed and the third group (T3) was treated as control. The data on haemogram were collected and analysed as per standard procedures. There was no significant difference between the treatment groups in the values of either haemogram or serum biochemical parameters during experimental period.